ANALISIS PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH BOS BERBASIS LITERASI KEUANGAN DI SMA NEGERI 1 TOMOHON - Allen Ch. Manongko; Listriyanti Palangda; Mawarta Nania Marisina (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2023)
ABSTRACT< span>< p> This study s goal is to describe in depth the BOS SMA administration at SMA Negeri 1 < span>Tomohon< span> in the coming year of 2022 In this article we will discuss the following topics in order: 1 planning for SMA BOS finances in SMA Negeri 1 < span>Tomohon< span>; 2 implementation; 3 monitoring and evaluation; and 4 reporting This research is a qualitative descriptive analysis Participants in this research comprised school administrators instructors and students from SMA Negeri 1 < span>Tomohon< span> Interviews and careful note taking are two common data collection methods The reliability of the data in this study was ensured by the use of triangulation and member checks Methods for < span>analyzing< span> the data include data reduction data presentation and verification of the resulting conclusions Based on the findings 1 the SMA Negeri 1 < span>Tomohon< span> school budget team develops the RKAS with input from the School Committee faculty and parents of SMA students in order to allocate SMA BOS money for 2022 The RKAS was ready at the same time as the SMA BOS RAB In 2022 there will be a two part process for distributing SMA BOS Funds: 2 implementation and 3 distribution Collecting funds as the high school s BOS Treasurer In accordance with the technical specifications laid forth in the SMA BOS 2022 schools may only utilize SMA BOS Funds to cover non operational school operations The team in charge of purchasing items and services does so effectively and efficiently The District Education Office and the School Committee are responsible for internal evaluation and oversight The outside implementation is the responsibility of the Provincial Education Office The SMA BOS LPJ will be used to report on the SMA BOS Funds for both semesters of 2022 < span>< p> Keywords: High School BOS Funds Planning Implementation Monitoring and Evaluation Reporting< span>< p> ABSTRAK< span>< p> < a>Tujuan< span> penelitian< span> ini< span> adalah< span> untuk< span> mendeskripsikan< span> secara< span>mendalam< span> pengelolaan< span> BOS SMA di SMA Negeri 1 < span>Tomohon< span> pada < span>tahun< span> 2022 < span>mendatang< span> Pada < span>artikel< span> ini< span>akan< span> dibahas< span> topik topik< span> berikut< span> secara< span> berurutan< span>: 1 < span>perencanaan< span> keuangan< span> BOS SMA di SMA Negeri 1 < span>Tomohon< span> ;< span> 2 < span>implementasi< span>; 3 < span>pemantauan< span> dan < span>evaluasi< span>; dan 4 < span>pelaporan< span> < span>Penelitian< span> ini< span> merupakan< span> penelitian< span>deskriptif< span> analisis< span> kualitatif< span> < span>Partisipan< span> dalam< span> penelitian< span> ini< span>terdiri< span> dari< span> pengelola< span> sekolah< span> < span>pengajar< span> dan < span>siswa< span> SMA Negeri 1 < span>Tomohon< span> < span>Wawancara< span> dan < span>pencatatan< span> yang < span>cermat< span> adalah< span> dua< span> metode< span> pengumpulan< span> data yang < span>umum< span> < span>Keandalan< span> data < span>dalam< span> penelitian< span> ini< span> dipastikan< span> dengan< span>menggunakan< span> triangulasi< span> dan member check < span>Metode< span>analisis< span> data < span>meliputi< span> reduksi< span> data < span>penyajian< span> data dan < span>verifikasi< span> kesimpulan< span> yang < span>dihasilkan< span> < span>Berdasarkan< span> temuan< span>tersebut< span> 1 Tim < span>anggaran< span> sekolah< span> SMA Negeri 1 < span>Tomohon< span>menyusun< span> RKAS < span>dengan< span> masukan< span> dari< span> Komite< span> Sekolah< span> < span>guru< span> dan orang < span>tua< span> siswa< span> SMA < span>untuk< span> mengalokasikan< span> dana BOS SMA < span>tahun< span> 2022 RKAS < span>sudah< span> siap< span> pada < span>saat< span> yang < span>sama< span> < span>waktu< span> sebagai< span> RAB SMA BOS Pada < span>tahun< span> 2022 < span>akan< span> ada< span> dua< span> proses < span>penyaluran< span> Dana BOS SMA: 2 < span>implementasi< span> dan 3 < span>penyaluran< span> < span>Mengumpulkan< span> dana < span>sebagai< span> Bendahara< span> BOS SMA < span>Sesuai< span> dengan< span> spesifikasi< span>teknis< span> yang < span>tertuang< span> dalam< span> BOS SMA 2022 < span>sekolah< span> hanya< span>dapat< span> menggunakan< span> Dana BOS SMA < span>untuk< span> membiayai< span>operasional< span> sekolah< span> yang non < span>operasional< span> Tim yang < span>bertugas< span> membeli< span> barang< span> dan < span>jasa< span> melakukannya< span> dengan< span>efektif< span> dan < span>efisien< span> < span>Dinas< span> Pendidikan < span>Kabupaten< span> dan < span>Komite< span>Sekolah< span> bertanggung< span> jawab< span> atas< span> evaluasi< span> dan < span>pengawasan< span>internal < span>Pelaksanaan< span> di < span>luar< span> menjadi< span> tanggung< span> jawab< span> Dinas< span>Pendidikan < span>Provinsi< span> LPJ SMA BOS < span>akan< span> digunakan< span> untuk< span>melaporkan< span> Dana BOS SMA < span>untuk< span> semester < span>kedua< span> tahun< span>2022 < span>< p> Kata < span>Kunci< span>: Dana BOS SMA < span>Perencanaan< span> < span>Pelaksanaan< span> < span>Pengawasan< span> dan < span>Evaluasi< span> < span>Pelaporan< span>< p>